2012
DOI: 10.1177/0042098012465905
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Urban Renaissance: New-build Luxury Developments in Berlin

Abstract: Inner-city living is a hot topic in Germany. Policy-makers long for new middle- and upper-class residents; evidence of urban in-flight has been documented by scholars, and debates on reurbanisation are in full swing. This trend has also led to the emergence of a new housing product in German metropolises: high-priced, centrally located and newly built apartment and townhouse developments. In this paper, these luxury developments are analysed as part of a general process of urban restructuring and a focus is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Consequently, although some argue that, due to the absence of direct displacement, new construction does not fall into the category of gentrification (Lambert, Boddy 2002;Hamnett 2003;Boddy 2007), we believe that it is rational to include newbuild developments into the framework of gentrification research. Such reasoning is also reflected in a wide range of studies that picked up the concept of new-build gentrification to describe new urban trends in cities like London (Davidson, Lees 2005, Montreal (Germain, Rose 2000;Rose 2002), in Swiss cities (Rerat et al 2010) or Berlin (Holm 2010;Marquardt et al 2013), but also in second-tier West European cities like Newcastle (Cameron 2003), Glasgow and Rotterdam (Doucet, van Kempen, van Weesep 2011) or, outside the West European/North American context, in Shanghai (He 2008), Cape Town (Visser, Kotze 2008) and Tokyo (Lützeler 2008). In post-socialist Europe, although new-build residential projects have been discussed in the works on socio-spatial change in the post-socialist city (Badyina, Golubchikov 2005;Cook 2010; Kovacs, Wiessner, Zischner 2012), new-build gentrification has not been studied systematically.…”
Section: Researching New Build Gentrificationmentioning
confidence: 99%
“…Consequently, although some argue that, due to the absence of direct displacement, new construction does not fall into the category of gentrification (Lambert, Boddy 2002;Hamnett 2003;Boddy 2007), we believe that it is rational to include newbuild developments into the framework of gentrification research. Such reasoning is also reflected in a wide range of studies that picked up the concept of new-build gentrification to describe new urban trends in cities like London (Davidson, Lees 2005, Montreal (Germain, Rose 2000;Rose 2002), in Swiss cities (Rerat et al 2010) or Berlin (Holm 2010;Marquardt et al 2013), but also in second-tier West European cities like Newcastle (Cameron 2003), Glasgow and Rotterdam (Doucet, van Kempen, van Weesep 2011) or, outside the West European/North American context, in Shanghai (He 2008), Cape Town (Visser, Kotze 2008) and Tokyo (Lützeler 2008). In post-socialist Europe, although new-build residential projects have been discussed in the works on socio-spatial change in the post-socialist city (Badyina, Golubchikov 2005;Cook 2010; Kovacs, Wiessner, Zischner 2012), new-build gentrification has not been studied systematically.…”
Section: Researching New Build Gentrificationmentioning
confidence: 99%
“…Davidson (2010, p. 532) concludes that spatial proximity has failed to foster mixing in the London Thamesfront newbuild areas; among other things, the availability of in-house services in newbuild developments limits the demand for local services. Similarly, Butler (2007) showed that the typical (affluent) resident of the Docklands development is completely uninterested in the immediate neighbourhood because his or her social networks largely link to the workplace, while Marquardt et al (2012Marquardt et al ( , p. 1541 indicate that luxury new-build developments are described as both urban at heart and protected from the negative externalities present in central Berlin.…”
Section: Newbuild Gentrification and Its Social Contoursmentioning
confidence: 99%
“…This has meant that city centres now have and experience "complex social realities" Marquardt et al (2013Marquardt et al ( , p. 1552. As such, matters of everyday living are a challenge in many city centres because people are attempting to live their (ordinary) daily lives in a different (extraordinary) setting -the revitalising neoliberal city centre.…”
Section: Living (In) the City Centrementioning
confidence: 99%